2012
DOI: 10.5114/pwki.2012.29650
|View full text |Cite
|
Sign up to set email alerts
|

Is there any relationship between serum γ-glutamyltransferase levels and premature coronary artery disease?

Abstract: Original paper/Artykuł oryginalnyA b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…No research study has investigated the association between the concentration of ALP and PCAD. In a study, as a supplementary analysis, no signi cant difference in concentration of ALP between the PCAD group and healthy controls was observed, which is in line with the result of our study [14].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No research study has investigated the association between the concentration of ALP and PCAD. In a study, as a supplementary analysis, no signi cant difference in concentration of ALP between the PCAD group and healthy controls was observed, which is in line with the result of our study [14].…”
Section: Discussionsupporting
confidence: 91%
“…Contrastingly, a study on 181 PCAD patients and 80 age and sexmatched controls demonstrated no signi cant difference between the concentrations of the GGT in the PCAD patients and controls. Moreover, the association between levels of the GGT and severity of the PCAD was investigated, and they came up with no signi cant differences between concentration of the GGT in patients with Gensini score ≤ 20 compared to those with Gensini score ≥ 20 [14]. The studies have small sample sizes and usually have been conducted in a tertiary center which may in uence the result of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation